Visual and graphic defragmentation of life and operational and production cycles of a construction enterprise according to standardized stages - Chupryna, Kh.; Derkach, A.; Rovenskyy, A.; Huliaiev, D. (Ways to Improve Construction Efficiency, 2022)
This article proposes a structured mechanism for forming the trajectory of the transformation of the construction enterprise management system. The system of indicators that currently assess the level of sustainability of the enterprise is described; a toolkit that allows you to use this system of indicators throughout the entire existence of the enterprise, taking into account the influence of multidirectional uncertainty factors that differ in the degree of influence, arising in the conditions of digitalization of the economy; the ability to determine the scenarios of the company's development depending on the degree of influence of uncertainty factors on its functioning; the ability to assess the effectiveness of the proposed management decisions to counteract these factors. The methodology of digitization of the administration of the activities of the construction enterprise - a stakeholder of construction projects - has been introduced and substantiated. The development of the enterprise, the leveling of the impact of actual and potential threats to the macro-environment through the rational use of all the benefits of the high stage of the life cycle have been studied. On the basis of the analysis of theoretical sources and the results of statistical analysis, a system of factors of scenarios for managing the economic potential of the enterprise with the qualitative characteristic of "proactivity" was determined: return on investment, the share of innovative types of products in the total number of products of the enterprise, the rate of renewal of fixed assets, profitability of production, profitability of production, return on capital , the coefficient of sustainability of financing. The development of adaptability, which is expedient at the stage of recession, is analyzed and involves the use of the company's capabilities to implement active rehabilitation measures in order to prevent stagnant processes and ensure a return to the stage of progression and prosperity in the shortest possible time. The following factors were determined for the scenarios of this group: quick liquidity coefficient, autonomy coefficient, maneuverability coefficient of working capital, suitability coefficient of the company's fixed assets, labor productivity, fund profitability.